A Case Study of Management of Ground Water Resources in India: Addressing the Challenges of Groundwater Management in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Groundwater in India, due to its nearly universal quality, constancy and ease of capital, is the most preferred water source in different customer areas. The developing dependence on groundwater as a solid wellspring of water has brought about the unpredictable extraction, regardless of water reviving capacity and other ecological components, of different pieces of the nation. Then again, there are territories in the country where, given the availability of sufficient resources, groundwater production is inoptimal as well as canal command areas with water logging difficulties and soil salinity due to the rising of soil water levels. Accordings to the most recent assessment are measured at 433 billion cubic meters (bcm) of the country's annual replenishable groundwater assets, of which 399 bcm is deemed usable for different uses. The irrigation industry also keeps 92 percent of its annual withdrawal as the largest consumer of ground water. The nation has extremely unequal groundwater production and there are major variations everywhere. Although the overall development stage is around 58, in Northwest Plain States (98), the average production of the soil is much higher than in the Eastern Plain (43) and Central Plain (42). In the Indian sense, the management of groundwater resources is an extremely difficult idea. The very uneven distribution and its use make it impossible for the country as a whole to have a single management strategy. Any practical management strategy for groundwater should include, depending on the regional climate, a combination of supply side and demand side steps. As regards the availability of water resources in the Eastern Plain, Orissa (part), West Bengal and the Eastern Pradesh, Delhi, Haryana and Punjab, West Uttar, Chandigarh are alluvial areas this is approximately 44 of the total resources available. The total amount of the water supplies available in the EasternPlain is approximately 42.9. Nevertheless, average results in these classes of states are 43 and 98 respectively. Because of the significant differences in the stage of groundwater in these areas, the factors responsible for technical and socio-economic imbalances must be critically analyzed. Those should also be included in the design of any systematic policies on water resource management. A number of Governments and Non-Governmental Agencies, social service organisations and stakeholders desperately need concerted efforts to develop an implementable plan to manage the valuable natural resource effectively.